Dietary Patterns and Their Socioeconomic and Behavioral Determinants in 6- to 8-Year-Old Portuguese Children - Rodrigues, D. (2016)
Adherence to a healthier diet is declining, with children consuming more saturated fats and simple carbohydrates. Factors influencing this choice were studied using a cross-sectional study with children (6 to 8 years old) living in Coimbra. Socioeconomic and behavioral factors were obtained from the parents. Dietary patterns of 1,063 children were identified: Mediterranean (MedDiet), saturated fats (SFatDiet), and base of Portuguese diet (BPDiet). Their relationship with socioeconomic and behavioral determinants was analyzed. SES determined strongly the dietary choices with lower SES being associated with higher consumption of SFatDiet and higher SES with BPDiet. Worse diet quality was shown to coexist with other unhealthy behaviors.